The Principle of Subsidiarity as a Valuable Benchmark in the Regulation of Economic Relations - Kondratienė, Virginija (Annales. Etyka w Życiu Gospodarczym, 2014)
The principle of subsidiarity can be an effective tool for adjusting economic systemsand establishing the social rule-of-law concept in public organisation. Inconsidering the usability of the principle of subsidiarity, the following aspectsthereof are discussed: the role in the development of the European social model;employment in determining limits for the powers of the public and private sectors;the application in the market and planned economy systems; and the social justicefunction in the development of a social welfare state.The principle of subsidiarity as an instrument for individuals’ interests, balancingand adjusting in the regulation of economic systems, helps to establish therelative sizes of public policy and the market, as subsidiarity can help ensurea more equitable distribution of public goods while guaranteeing the maintenanceof the creative potency of operators and minimal satisfaction of vital needs ofindividuals unable to contribute to the production of goods. It amounts to a constitutionalmeasure determining the balance of productive and protective state, thusensuring the stability of the state organisation.In the concept of a social rule-of-law state, subsidiarity draws clear limits tothe state’s powers, institutionally bringing together efforts of all members of thecommunity to achieve welfare in the state.